The increasing role of abdominal metastesectomy for malignant melanoma in the era of modern therapeutics. (September 2022) - Mor, Eyal; Laks, Shachar; Assaf, Dan; Asher, Nethanel; Ben-Betzalel, Guy; Grynberg, Shirly; Stoff, Ronen; Adileh, Mohammad; Steinberg-Silman, Yael; Shapira-Frommer, Ronnie; Schachter, Jacob; Nissan, Aviram; et al.
Abstract: Background: Metastatic spread of malignant melanoma to the abdomen presents a therapeutic challenge. Targeted and Immune-therapies dramatically improve patients' survival, yet some patients may still benefit from surgical intervention. This study investigates the outcomes of surgical treatment of abdominal metastatic melanoma in the era of modern therapy. Methods: This is a retrospective study of all patients who underwent surgical resection for abdominal metastatic melanoma between the years 2009–2021 (n = 80). We examined the clinical, operative, perioperative, and oncological outcomes of these patients. Results: The cohort included a therapeutic group (T, n = 43) and palliative group (P, n = 37). The rate of overall post-operative complications was lower in the T group (n = 3, 9.3%) compared to the P group (n = 10, 27.1%) (p = 0.04), but no difference in major complications rate (p = 0.41). The median follow-up was 13.4 months (range, 0.5–107), with an estimated 2- and 5-years survival of 66.5% and 45.3% respectively. The estimated 2- and 5-years survival of the T group was 76.61% and 69.65%, and 49.01% and 28.01% in the P group (p = 0.005). Univariate analysis identified Therapeutic resection (HR 3.2, p  = 0.008), isolated lesions (HR 1.47, p  = 0.033) and major complication score (HR 1.8, p=<0.001) to be correlated with survival. On multivariate analysis, Therapeutic resection (HR 2.53, p  = 0.042) and major complication score (HR 1.62, p  = 0.004) remained significant independent factors correlated with survival. In patients who progressed on treatment, and their progression was treated with surgical resection 46.1% where able to be maintained on the same preoperative treatment strategy. Conclusion: We have demonstrated that abdominal metastesectomy is a safe and oncologically efficacious therapy in selected patients. Especially in the era of modern therapeutics, patients with isolated disease site, limited resectable progression on therapy, or patients with symptomatic metastases should be considered for surgical resection.